Identification and molecular marker analysis of PHS resistance of high generation wheat materials - Zhou, Heng; Zhang, Qiqi; Liu, Fangfang; Cao, Wenxin; Li, Yao; Wan, Yingxiu (Scientific reports, 2025)
Pre-harvest sprouting (PHS) of wheat will significantly reduce the yield and quality of wheat and threaten the safety of wheat production in China. Screening and utilization of resistant germplasm and functional molecular markers is the fundamental way to reduce the harm of PHS. In this study, 238 high generation lines were used to identify and evaluate PHS resistance by grain germination method, and the distribution of PHS function markers Vp1B3 , myb10-D , PM19-A1 and MFT-A2 in resistant germplasm was determined and their breeding effects were evaluated. Phenotypic identification showed that there were significant differences in the relative seed germination index (RSGI) of 238 wheat germplasm resources. The RSGI ranged from 0.03 to 1, and the average RSGI was 0.31. The difference significance analysis showed that the RSGI of the alleles of functional markers Vp1B3 , PM19-A1 and MFT-A2 were significantly different, suggesting that Vp1B3 , PM19-A1 and MFT-A2 could be used for detection of PHS resistance genotypes and marker-assisted breeding. Based on the phenotype and genotype results, three red wheat materials with high PHS resistance (23JD392, 23JD393 and 23JD481) and four white wheat materials with high PHS resistance (23JD025, 23JD085, 23JD541 and 23JD655) were selected. At the same time, the high resistance materials 23JD392 and 23JD393 which amplified TaVp-1Bc / TaPM19-A1a / TaMFT-A2a had the lowest RSGI. These results can be used for genetic breeding and layout of wheat varieties resistant to PHS, indicating that resistance can be significantly improved by using functional markers. This study combined molecular markers and phenotypic identification to screen anti-PHS materials, which is expected to improve the level of wheat PHS resistance.